Early Political Development in Mesopotamia - Jacobsen, Th.
1. Introduction: Desiderability of Inquiry, Special Conditions of Mesopotamian History, Limited Goals of Inquiry — 2. Country and Settlement: Country, Settlement — 3. Earliest Political Pattern. Primitive Democracy: Sources, Primitive Democracy, Exten- sion of Pattern, Date of Maximal Extension — 4. Germs of New Direction — 5. Developing Political Forms. Primitive Monarchy: Sources, Ascendency and Perpetuation of Offices, Evaluation. Vulnerability of Assembly. New Type of Power — 6. Palace Records from Shuruppak — 7. The Tendency for Primacy: Development by Beginning of Early Dynastic III, Regional Kingdoms, Hegemony (Kings of Kish), Nature of the “Kingship of Kish” — 8. Conclusion: Summary of the Early Development, Primitive Empire (Akkade), Bureaucratic (National State (Ur III), Dissolution into Regional Kingdoms (Isin, Larsa), Catastrophe in South (Political Stagnation), The Assyrian Empire.